The Concept of Profit Sharing on Deposits Sharia in Islamic Bank for Non-Muslim Market - Moh Farih Fahmi; Binti Mutafarida; Ahmad Hanif Fajrin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
A concept of an ideal alternative solution to Islamic banking that is less attractive, especially in sharia deposit fund investment products, is certainly an issue that must be resolved immediately. The concept of Islamic banks that should be oriented towards rahmatan lil alamin certainly must be open to all humanity, including non-Muslims. The customers' insecurity towards sharia bank deposit products is one of the reasons for this is "unrepresentation" or incompatibility of Islamic banking towards the desire of non-Muslim customers to discuss profit agreements in Islamic banking. This is evidenced by Islamic bank products in the form of sharia deposits that only use mudhorobah contracts. This agreement emphasizes that profits cannot be determined at the beginning like conventional banks, this is a problem for non-Muslim customers. Therefore, as a form of rahmatan lil alamin orientation, Islamic banking needs to find a solution so that non-Muslims want to put deposit funds in Islamic banks by using fixed profits and can be determined in the beginning but do not violate Islamic teachings. So in this paper we will discuss a solution solution for sharia deposit contracts using murabahah contracts, especially for non-Muslim customers whose studies are supported by theories whose references are valid and relevant literature